Budget Transparency in Costa Rica during the Period 2003–2009 - Palma Rodríguez, Carlos (2011)
This article discusses the main results of the study on transparency in public budgets in Costa Rica and the evolution of the main attributes that make it up in the period 2003-2009, as an important element within the new concept of public management. The modern view of involving the public as an actor in the process of public policy requires us to develop new models budget to make their public administration, efficient, effective, controllable and more democratic. The study notes that thecountry is moving increasingly to value the attributes of transparency, but it reflects air criticism, citizen participation in budgeting, accountability and allocation of public budgets.